(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Objective: This prospective clinical study was conducted between July 2003- June 2005 at Dhaka Medical College Hospital, Dhaka, Bangladesh to make a comparative evaluation of the outcome of skin graft on patients of postburn contractures of the fingers using integrated scores for measuring several outcomes together. Materials & Methods: A total of 56 subjects of postburn contractures of the fingers were selected consecutively and were evaluated at baseline by number of digits affected, surface area involved, extension deficit, fingers with maximum extension deficit and duration of contracture. Thirty two subjects were assigned to Full-thickness skin graft group (Group-A) and 24 to Split-thickness skin graft group (Group-B). Respective graft coverage was applied to the wound following release of contracture. Immediate outcome was evaluated in terms of graft take and number of graft-site complications, while follow up outcome was evaluated in terms of extension deficit six months after correction using specific scores for defined outcome. Results: Over 70% of the subjects were < 15 years with mean ages of Group-A and Group-B were 9.38 ± 1.66 and 9.94 ± 1.42 years respectively. In both groups maximum extension deficit was found in little finger (78% in Group- A and 54% in Group-B). The Interphalangeal (IP) joints were observed to be most frequently involved (78% in Group-A and 75% in Group-B). The duration of contracture, number of digits involved and surface area of the fingers involved were almost identically distributed between the groups. Outcome shows that donor-site morbidities (discolouration and hypertrophic scars) were significantly less in Group-A compared to that in Group- B (p < 0.001 and p = 0.047). Similarly the Group-A was significantly superior compared to Group-B in terms of minimal extension deficit (0 - 10°) 6 months after correction (59.4% vs. 25%, P < 0.05). About two-third of the subjects in both the groups demonstrated 100% graft take and around 80% had 2 or < 2 graft-site morbidities. The excellent outcome was significantly higher in Group- A (37.5%) than that in Group-B (12.5%) (p < 0.05). Conclusion: Full-thickness skin graft is a better option of intervention than Split-thickness skin graft for coverage after release of contracture. However, the findings need to he validated by a larger sample size. Key words: Postburn flexion deformity, full-thickness skin graft, split-thickness skin graft, graft take, donor-site morbidity, graft-site morbidity and extension deficit. DOI: 10.3329/jbcps.v27i1.4240 J Bangladesh Coll Phys Surg 2009; 27: 25-29